1982
DOI: 10.1161/01.hyp.4.5.620
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular volume expansion in the development of DOC-salt hypertension in the rat.

Abstract: SUMMARY Changes in inulin space, plasma and blood volume, exchangeable and "noninulin" sodium were studied during the prehypertensive, early and late hypertensive stages of deoxycorticosterone (DOC)-saJt administration in the rat. The effect of an acute water load in previously nephrectomized animals was also studied. Hypertension developed after 1 to 2 weeks of the DOC-salt regimen and was always preceded by enlargement of the inulin space and increased plasma and blood volume. Expansion of extracellular flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, according to VILLAMIL et al (1982), extracellular volume, plasma volume, and blood volume were all greater only in rats in which arterial pressure did not elevate in the first 1-2 weeks of DOCA and salt administration or in those in which it elevated at last in the 4th-6th week. These variables were almost normal in rats in which arterial pressure had risen in the first 1-2 weeks.…”
Section: Discussionmentioning
confidence: 86%
“…However, according to VILLAMIL et al (1982), extracellular volume, plasma volume, and blood volume were all greater only in rats in which arterial pressure did not elevate in the first 1-2 weeks of DOCA and salt administration or in those in which it elevated at last in the 4th-6th week. These variables were almost normal in rats in which arterial pressure had risen in the first 1-2 weeks.…”
Section: Discussionmentioning
confidence: 86%
“…The hypertension that develops as a result of salt retention, as in mineralocorticoid hypertension, is always preceded by increased plasma volume (42,113). In the chronic state, the elevated BP promotes a pressure natriuresis so that normal ECF volume is restored at the expense of (chronically) elevated pressure (110).…”
Section: Salt Plasma Volume and The Kidneysmentioning
confidence: 99%
“…Mineralocorticoid excess, which causes salt and water retention (42,113), induces hypertension in humans (59). DOCA-salt hypertension, in which uninephrectomized animals are administered DOCA and placed on a high-salt diet, is a common model of hypertension in mice, rats, and other animals.…”
Section: Ouabain Antagonism As a Therapy For Hypertensionmentioning
confidence: 99%
“…They proposed that NaCl levels or plasma osmolality triggered sympathoexcitation, leading to hypertension. While it has been reported that DOCA–salt hypertension is characterized by a small but significant, sustained increase in plasma sodium (Möhring et al 1972; Villamil et al 1982), others reported a small but significant increase only when plasma sodium and chloride were combined (O'Donaughy & Brooks, 2006). Even small increases in plasma sodium can enhance sympathetic tone, supporting a role for increased SNA in DOCA–salt hypertension.…”
mentioning
confidence: 99%